Modified Hydraulic Table / Acapulo, Hope Earl L.... [et al.]. - Acapulco, Hope Pearl L.; Agustin, Junior R.; Dela Cruz, Ronnie May B.; Taningco, Julius Ceasar C.; San Felipe, Kole U.; San Juan, Verlee B. (2024)
The main objective of this study is to develop a Modified Hydraulic Table specifically it sought to design and construct, perform try-out and revision, determine the level of performance, determine the level of acceptability and developed a user$1 (Bs manual intended for the unit. This study was conducted in the year 2022- 2023, while the subjects of the study were five (5) Automotive, three (3) Mechanical, two (2) Electrical Technology experts and twenty (20) end - users, chosen through purposive sampling. The study used the descriptive quantitative survey method with the modified questionnaire- checklist validated by the experts was used as the main instrument in gathering the needed data. The data were gathered, tabulated, and interpreted using qualitative discussion method, and mean as the statistical treatments, to design and construct the modified hydraulic table, to present try-out and revision, and to develop user$1 (Bs manual, qualitative discussion method was used, and mean was used to determine the level of acceptability of modified hydraulic table with respect to different variables. In the design and construction of the Modified Hydraulic Table, the working drawings on how to construct each part of the project was used as guide for constructing the project. The Modified Hydraulic Table was built using locally available materials. Additionally, it is electrical and automatic hydraulic operated. It is also powered by 12 volts battery. The maximum capacity of the Modified Hydraulic Table is 100 kilograms and can be operated indoors and outdoors. Lastly, it could be used in carrying heavy duty equipment and a working table. In the try-out and revision, the developed Modified Hydraulic Table went through series of try outs and revisions to determine the design, durability, functionality, portability, safety and maintenance of the project. Few revisions were done and finally its purpose was obtained. In terms of the load lifting capacity in kilograms as evaluated by the researchers in the modified hydraulic table, the table is extremely capable and can lift up to 100 kilograms load. The researchers provided a detailed user$1 (Bs manual wherein the short reminders, maintenance, specifications and instructions are included. The user$1 (Bs manual includes all the information about the product. It provides instructions on how to properly use and maintain the product. The Modified Hydraulic Table performed within standard level in terms of load lifting capacity and extremely acceptable in terms of design, durability, functionality, portability, safety and maintenance.s
Thesis